Desenvolvimento de imunolipossomas anti-EGFR PH-sensíveis para liberação de docetaxel e avaliação anticancerígena em linhagens de células de câncer de próstata - Moreira, Thais da Silva (2024)
Docetaxel (DTX) is an antineoplastic agent used to treat prostate cancer. However, as it is not very selective and has high lipophilicity, patients' adherence to chemotherapy is limited. In this way, liposomes functionalized with cetuximab enable targeted therapy for the epidermal growth factor receptor (EGFR), which is overexpressed in the membrane of prostate cancer cells. Thus, the present work aimed to develop pH-sensitive immunoliposomes containing docetaxel, carry out their physicochemical characterization and verify their in vitro efficacy in prostate cancer cell lines. To optimize conjugation to the antibody, the following lipid composition was used: soy phosphatidylcholine (SPC), dioleoylphosphatidylethanolamine (DOPE), cholesteryl hemisuccinate (CHEMS) and diestearoylphosphatidylethanolamine associated with polyethylene glycol and maleimide (DSPE-PEGMAL). The immunoliposome results showed an average particle size of 100.46 nm ± 1.01; polydispersity index (PDI) of 0.16 ± 0.01; zeta potential of -15.80 mV ± 0.88, encapsulation efficiency (EE%) of 81.81 ± 12.5 and conjugation efficiency (EC%) of 33.84 ± 2.58. In the pH sensitivity study, a 66.9% increase in immunoliposome size was observed at pH 6.4 (tumor) and a 99.2% increase at pH 5.0 (endosomal) after 24 hours of incubation. In thermophoresis, the inflection points of cetuximab were restricted in the immunoliposome samples, which can demonstrate the conjugation of the antibody to the nanoparticle and the maintenance of the structure and stability of the antibody, ensuring its structure and activity. The indirect ELISA assay suggested that cetuximab was successfully conjugated to the liposome in the correct conformation to maintain its EGFR binding functionality. In relation to the cell solution, the immunoliposome showed a greater cytotoxic effect for the DU145 cell (EGFR overexpression), with an IC50 of 6.17 ± 1.19 nM, when compared to the liposome and docetaxel solution (11.17 ± 1. 05 nM and 21.40 ± 3.29 nM, respectively). In the PC3 lineage (low expression of EGFR), the DTX immunoliposome reached an IC50 of 66.82 ± 11.59 nM while the liposome and docetaxel presented an IC50 of 110.60 ± 19.79 nM and IC50 of 37.54 ± 3, 48 nM, respectively. Internalization of the immunoliposome was rapid (15 minutes) and greater (70.17% ± 2.55) when compared to that of the liposome (32.20% ± 0.95) in the DU145 cell line. Thus, based on these results, it was possible to obtain an immunoliposome formulation with adequate physicochemical characteristics and maintenance of antibody integrity, providing, as expected, a reduction in the prediction of metastatic prostate cancer cells, with high cellular internalization in cells. that overexpress EGFR.